Regulation of Fasting Blood Glucose, Insulin, and Homa-Ir in Relation to Malnutrition Among the Elderly: Mechanisms and Clinical Implications - Kosasih, Robert; Sari, Triyana; Santoso, Alexander Halim; Jap, Ayleen Nathalie; Hartono, Vincent Aditya Budi; Syarifah, Andini Ghina (Pusat riset dan Inovasi Nasional, 2025)
Malnutrition significantly disrupts metabolic processes like fasting blood glucose (FBG) regulation, insulin secretion, and insulin resistance (HOMA-IR), especially among the elderly. Aging amplifies these effects through declining β-cell function, reduced insulin sensitivity, and chronic inflammation, increasing the risk of type 2 diabetes and cardiovascular diseases. Globally, malnutrition affects 22% of the elderly, with prevalence reaching 28% in Indonesia due to food insecurity, limited healthcare access, and poor nutrition education. Malnutrition exacerbates glucose-insulin imbalances by causing muscle loss, increasing FBG levels, and inducing insulin resistance through chronic inflammation. Despite its impact, critical knowledge gaps remain, particularly in low- and middle-income countries like Indonesia. This study investigates how malnutrition affects FBG, insulin levels, and HOMA-IR in elderly individuals, focusing on mechanisms like inflammation and muscle loss to inform targeted interventions and improve metabolic health in resource-limited settings. This cross-sectional study evaluated fasting blood glucose, insulin, and HOMA-IR among 31 elderly participants at Panti Werdha Santa Anna. The study found no significant differences in fasting blood glucose, fasting insulin, HOMA-IR, or HbA1c levels across Mini Nutritional Assessment categories (normal, at risk, malnourished; p > 0.05). These results suggest no strong association between nutritional status and metabolic parameters, highlighting the need for further research with larger samples. This study finds no significant association between nutritional status and glycemic control in the elderly, suggesting malnutrition's indirect impact via mechanisms like inflammation and muscle loss. Comprehensive nutritional assessments remain essential to understanding its effects on metabolic health.